A software tool for algebraic design of interval systems control. (27th December 2010) - Matusu, Radek
This paper intends to describe a software tool for algebraic design of continuous-time control under assumption of interval plants. The program takes advantage of the MATLAB + Simulink + Polynomial Toolbox environment and it represents an easy but effective and user-friendly way to control synthesis, robust stability analysis and simulation. The product, which can be used both for research and educational purposes, is freely available on the internet.